Segurança e cidadania no México: Proposta para um exercício efetivo da cidadania - Ramírez Martínez, Eduardo Aristóteles (DIXI, 2021)
Purpose: The text is a proposal to strengthen citizen capacities in security matters in the Mexican context. Description: The increase in violence and crime rates requires a more participative citizenry with greater tools to collaborate with the authorities. Therefore, it seeks to empower citizens to help the authorities, through the assessment of technical and human rights elements, in order to monitor security and government actions in this area. Point of view: The proposal seeks to empower and legitimize citizens as valid observers and interlocutors. Conclusions: With this possibility, we believe security levels will improve significantly.